Analysis of the Role of Youth Fishermen Catching the Marine and Fishery Sector in Regional Development in Langkat District - Said Reza Pahlevi; H.B. Tarmizi; Tavi Supriana (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
The purpose of this study was to determine and analyze the role of youth, the problems faced by youth and youth strategies in developing marine fisheries resources in Langkat Regency. The research method used is quantitative research, using research populations from three sub-districts in Langkat Regency, namely Tanjung Pura, Pangkalan Brandan, and Secanggang, with a total sample of forty people. Furthermore, the data obtained is then analyzed with a single diagram analysis and also using a SWOT analysis. The factors that influence the problems of youth in the fisheries sector in Langkat Regency based on research are the problem of low education, lack of education in fisheries training, less advanced fishing gear, damage to coral reefs, still rampant fishing with fishing gear that is not environmentally friendly. The role of youth as agents of change, agent of development and agent of modernization simultaneously has a significant positive effect on the development of the marine and fisheries sector in Langkat Regency. The strategy of the marine and fisheries sector youth in Langkat Regency is to manage marine fisheries resources as tourism objects, carry out management based on an ecosystem approach, manage marine fisheries resources based on environmentally friendly technology, and increase productivity based on environmentally friendly knowledge and technology.